Penskoran, Nilai, Norm-Referenced dan Criterion Referenced - Nurpaidah, Anis; Restijuana, Fera; Ramadhani, Suci; Sudrajat, Yayan (SINAU : Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2022)
Scoring can be said as giving a number whose existence is as important as the preparation of the test. Assessment as a structuring process to interpret what has been achieved by students so that a decision can be taken. In general, scores and grades have differences, namely scores are the result of scoring work which is obtained by adding up the numbers of students' correct answers in each test. The value is part of the score that is converted into numbers by applying certain references. When setting values, there are two types of orientation in evaluation that need to be considered, namely Norm-referenced and Criterion-referenced. Norm referenced is a rating based on a particular section/group. Meanwhile, Criterion-referenced is to provide direction regarding what students have mastered, so that it is not group-oriented but results-oriented. This study uses literature study techniques by collecting documents from digital libraries.